An untamed state - Gay, Roxane (Black Cat, 2014)
Mireille Duval Jameson is a rich and self-assured Haitian woman who is kidnapped by a gang of heavily armed men. Held captive by a man who calls himself the Commander, Mireille must endure his torment until her unwilling father pays up.